1999
DOI: 10.1007/s004210050604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrifuging at 2g on rat long bone metaphyses

Abstract: Hypergravity may be considered as a means of counteracting the deleterious effects of microgravity on bone tissue. The effects of exposure to 4 days of hypergravity provided by centrifuging, on bone tissue were studied using histomorphometry. Young 53-day-old male Sprague Dawley rats were randomly divided into a centrifuged group (2g, n = 10), a rotated group (ROTATE, n = 6) of rats exposed to 1.03 g placed in cages near the centre of rotation of the centrifuge and a stationary control group (CONTROL, n = 10).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Meanwhile, the developing cartilage was shown to respond to gravitational changes according to Hert's curve (8,22,23), in which an increased baseline loading reduces cartilage differentiation, while a reduced baseline loading leads to increased differentiation, but only within a range, beyond which lack of differentiation results. This may account for the altered cell shapes seen in our centrifuged cartilages, similar to findings that were previously reported by Vico et al (36) in a study involving excess G loading. At least in our study, the main effects of mechanical stress upon cartilage seem to be changes in extracellular matrix and in cell-to-matrix adhesion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, the developing cartilage was shown to respond to gravitational changes according to Hert's curve (8,22,23), in which an increased baseline loading reduces cartilage differentiation, while a reduced baseline loading leads to increased differentiation, but only within a range, beyond which lack of differentiation results. This may account for the altered cell shapes seen in our centrifuged cartilages, similar to findings that were previously reported by Vico et al (36) in a study involving excess G loading. At least in our study, the main effects of mechanical stress upon cartilage seem to be changes in extracellular matrix and in cell-to-matrix adhesion.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays, mankind's enterprises in space are no longer science fiction, but significant biological, psychological and environmental problems are yet to be addressed (25). The deleterious effects of spaceflights and microgravity upon the musculoskeletal system have been well-documented (13,20), and hypergravity can be considered a valuable means of counteracting those (36).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported the effects of hypergravity on the long bones of growing rats (Kohles et al, 1996;Martinez et al, 1998;Smith, 1975;Vico et al, 1999) and growing dogs (Doden et al, 1978;Oyama, 1975). Martinez et al (1998) reported that hypergravity shortened the length of the femurs and reduced the cortical bone area in young growing rats, but the bone density at the femoral mid-diaphysis was unchanged.…”
Section: Introductionmentioning
confidence: 95%
“…This indicates that an increase in body weight is associated with an increase in endochondral bone formation. Similarly, both treadmill exercise and hypergravity (Vico et al, 1999) have been reported to increase the bone volume of the primary spongiosa in growing rats. However, the interpretation of these experiments is not straightforward, since the hypergravity seemed to have an effect apart from the induced change in loading (Vico et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, both treadmill exercise and hypergravity (Vico et al, 1999) have been reported to increase the bone volume of the primary spongiosa in growing rats. However, the interpretation of these experiments is not straightforward, since the hypergravity seemed to have an effect apart from the induced change in loading (Vico et al, 1999). In addition, weight loading has been reported to promote growth plate ossification in chicks (Reich et al, 2005), but as the loading also increased vascularization and altered chondrocyte gene expression, this cannot solely be attributed to an osteocyte response.…”
Section: Discussionmentioning
confidence: 97%